Successful Treatment of Small Intestinal Bleeding in a Crohn’s Patient with Noncirrhotic Portal Hypertension by Transjugular Portosystemic Shunt Placement and Infliximab Treatment - Benjamin Heimgartner; Heather Dawson; Andrea De Gottardi; Reiner Wiest; Jan Hendrik Niess (Case Reports in Gastroenterology, 2016)
Small intestinal bleeding in Crohn’s disease patients with noncirrhotic portal hypertension and partial portal and superior mesenteric vein thrombosis is a life-threatening event. Here, a case is reported in which treatment with azathioprine may have resulted in nodular regenerative hyperplasia, portal hypertension and portal vein thrombosis. The 56-year-old patient with Crohn’s disease developed nodular regenerative hyperplasia under treatment with azathioprine. He was admitted with severe bleeding. Gastroscopy showed small esophageal varices without bleeding stigmata. Blood was detected in the terminal ileum. CT scan revealed a partial portal vein thrombosis with extension to the superior mesenteric vein, thickening of the jejunal wall and splenomegaly. Because intestinal bleeding could not be controlled by conservative treatment, the thrombus was aspirated and a transjugular intrahepatic portosystemic shunt (TIPS) was placed. Switching the immunosuppressive medication to infliximab controlled Crohn’s disease activity. Bleeding was stopped, hemoglobin normalized, and thrombocytopenia and bowel movements improved. In summary, small intestinal bleeding in a Crohn’s patient with nodular regenerative hyperplasia, portal hypertension and portal vein thrombosis can be efficiently treated by TIPS. TIPS placement together with infliximab treatment led to the improvement of the blood panel and remission in this patient.